Structural insights into ClpP protease side exit pore‐opening by a pH drop coupled with substrate hydrolysis. (20th May 2022) - Kim, Leehyeon; Lee, Byung‐Gil; Kim, Minki; Kim, Min Kyung; Kwon, Do Hoon; Kim, Hyunmin; Brötz‐Oesterhelt, Heike; Roh, Soung‐Hun; Song, Hyun Kyu
Abstract: The ClpP serine peptidase is a tetradecameric degradation molecular machine involved in many physiological processes. It becomes a competent ATP‐dependent protease when coupled with Clp‐ATPases. Small chemical compounds, acyldepsipeptides (ADEPs), are known to cause the dysregulation and activation of ClpP without ATPases and have potential as novel antibiotics. Previously, structural studies of ClpP from various species revealed its structural details, conformational changes, and activation mechanism. Although product release through side exit pores has been proposed, the detailed driving force for product release remains elusive. Herein, we report crystal structures of ClpP from Bacillus subtilis (BsClpP) in unforeseen ADEP‐bound states. Cryo‐electron microscopy structures of BsClpP revealed various conformational states under different pH conditions. To understand the conformational change required for product release, we investigated the relationship between substrate hydrolysis and the pH‐lowering process. The production of hydrolyzed peptides from acidic and basic substrates by proteinase K and BsClpP lowered the pH values. Our data, together with those of previous findings, provide insight into the molecular mechanism of product release by the ClpP self‐compartmentalizing protease. Synopsis: Delineating the mechanisms of substrate engagement and product release is essential for understanding the role of the conserved ClpP protease in protein homeostasis and developing antibiotics. This study shows that the opening of ClpP side exit pores is coupled to a pH decrease caused by peptide accumulation in the proteolytic chamber. Substrate hydrolysis by proteases lowers intra‐compartmental pH value by generating a large number of peptide products. Crystal structures show BsClpP in complex with an unforeseen number of acyldepsipeptides (ADEPs). Cryo‐EM structures of BsClpP at different pH values and in ADEP‐bound conditions reveal various structural features. Side exit pores of BsClpP are gradually enlarged upon pH lowering. Abstract : Conformational changes linked to peptide‐mediated acidification suggest a mechanism for proteolytic product release by a key bacterial and mitochondrial ATP‐dependent Clp protease system.